PERANCANGAN MEDIA PEMBELAJARAN AKSARA JAWA PADA SISWA SD MUHAMMADIYAH WELERI - Eka Maleka Hayati (STEKOM PRESS, 2018)
This study aims to design learning media that can increase enthusiasm, motivation and understanding of students towards Javanese script material, as well as media that can be used by teachers in learning Javanese language learning activities by reading Javanese characters and their partners. The method used by researchers is the R&D (Research and Development) method while the method used in the development of instructional media is the waterfall method. The material presented in the Javanese script learning media are (1) Introduction of Javanese script, (2) Sandhangan, (3) Couples, (4) Swara script, (5) Wilangan. In making learning media researchers used Adobe Flash CS6 software, CorelDraw X5, Adobe Photoshop CS6 and Adobe audition CS6, with the final product being an interactive CD (Compact Disk). Validation test from material experts and media experts got the criteria of